Potential effects of climate change on carbon storage in Iran based on climate and soil carbon models - Farzanmanesh, Raheleh (2012)
Soil organic carbon (SOC) is an important carbon pool, with the potential to drive large positive climate feedbacks. Climate change has the potential to alter terrestrial carbon storage since changes in carbon dioxide (CO2) concentrations, temperature and precipitation could affect carbon inputs to soil, and soil carbon decomposition rates. This study aimed to investigate the potential effect of changes in temperature and precipitation on soil organic carbon in selected parts of Iran. For this aim, 19 climatic stations were chosen across the study area to determine trends in the longterm annual mean temperature and precipitation series. All stations showed increase in mean annual temperature during the 20 year period from 1986 to 2005. Garmsar, ferdous, Ramsar and Birjand with +3.25°C, 2.1°C, 1.65°C and 1.3°C, respectively had the highest increase. The annual precipitation trend illustrated that the decreasing trends mostly happened in the arid and semi arid regions of the study area such as Mashhad, Gonabad, Ferdous, Semnan, Sabzevar, Shahroud and Torbat Heydarieh. To assess the influence of soil organic carbon under a changing climate,two climate change scenarios (A2 and B2) were used in the LARS-WG weather generator. The applied climate change scenarios were from the HadCM3 global climate model for the period 2011-2030. The evaluation of LARS-WG model was assessed by comparing between observed data and simulated data and their standard deviation. The evaluation between selected statistics of observed climate data and climate data generated by the model for both scenarios indicates that LARS-WG can predict the daily minimum and maximum temperatures better than daily precipitation. Climate change scenarios from this model indicated that temperature in the future will continue to increase (0.5°C-1.8°C). Precipitation is projected to decrease in the future for arid and semi arid regions (11%) but it will increase in northwest of the study area in future. Prediction of temperature and precipitation for the period 2011-2030 was used as an input for RothC model to show soil organic carbon changes under climate change scenarios (A2 and B2). SOC in the study area accounted for 106.2 t C/ha. The results showed that soil organic carbon will generally decrease during next two decades. Simulations produced the following results: (i) The decrease rate of soil organic carbon in cultivated lands was higher than other biomass under A2 and B2 scenarios. (ii) Soil organic carbon would decrease from 8.45 t C/ha and 13.37 t C/ha by the year 2020 and 2030, respectively, under A2 scenario. It would decrease from 7.34 t C/ha, and 11.77 t C/ha by the year 2020, and 2030, respectively, under B2 scenario. (iii) The rate of SOC changes over time under B2 scenario was minimal during 2005-2030 in comparison with A2 scenario. (iv) This study found an additional released carbon from soil to the atmosphere under A2 scenario than B2 scenario. The results showed that the rate of additional CO2 released to the atmosphere was highest in cultivated lands in both scenarios. The results also indicated that in the zones where precipitation and temperature have provided a better condition for SOM decomposition, the release of CO2 to the atmosphere takes place at a higher rate. Modeling results from this study show that changes in temperature and precipitation can influence on soil organic carbon and RothC model can be used to calculate annual carbon inputs and SOC changes in different geographical regions.